Corneal deflection amplitude and visual field progression in primary open-angle glaucoma - Jung, Younhea (PLoS One, 2019)
PURPOSE: To investigate the relationship between corneal deflection amplitude and visual field progression rate in patients with primary open-angle glaucoma (POAG). METHODS: This study included 113 eyes of 65 patients with POAG followed for an average of 4.81 ± 1.24 years. Evaluation of visual field progression rate was performed using mean deviation of standard automated perimetry. Corneal deflection amplitude was measured using Corvis ST (Oculus Optikgeräte GmbH, Wetzlar, Germany). Linear mixed models were performed to determine the relationship between corneal deflection amplitude, intraocular pressure (IOP), and visual field progression rate. RESULTS: Mean age was 56.36 ± 14.58 years. Baseline average mean deviation was -8.20 ± 9.12 dB and mean treated IOP was 14.38 ± 3.08 mmHg. Average deflection amplitude was 0.90 ± 0.13 mm. In both univariate and multivariate analysis, IOP (P = 0.028 and P < 0.001, respectively) and deflection amplitude (P = 0.034 and P < 0.001, respectively) significantly affected visual field progression rate. Eyes with high IOP and greater deflection amplitude showed faster progression rate. CONCLUSIONS: Corneal deflection amplitude was significantly related with glaucoma progression. Eyes with greater corneal deflection amplitude showed faster visual field progression rate in patients with POAG.